Avaliação da retração autógena de concretos de alto desempenho produzidos com cinza da casca de arroz - Vieira , Amanda Pereira (2018)
Some studies have attributed to the porous morphology structure of the rice husk ash (RHA) its capacity to retain water and reduce the self-desiccation of concrete. However, the ideal particle size (D50) and the cement partial replacement level to reduce autogenous shrinkage are not well specified, and also if the different residual carbon contents present in the RHA can affect these results. In this study, a 65 MPacompressive strength concrete was produced aiming the study of autogenous shrinkage. For this, two experimental stages were established. In the first stage, the influence of D50 and cement replacement by RHA was evaluated through a 22 -factorial design with a central point. The cement replacement levels varying from 8 to 12% and D50 ranging from 7 to 20 μm were selected. A concrete without mineral admixture and another with silica fume were used as references. In the second stage, the influence of 0.5, 6 and 12% of loss on ignition on RHA on autogenous shrinkage of concrete containing was evaluated. The results indicated two conditions for reducing concrete autogenous shrinkage: (i) ultrafine particles should be used at low replacement levels; (ii) ashes with D50 greater than 14 μm could replace the cement at high contents. The concrete with 12% of 20 μm-RHA was considered the optimal since this mixture presented the higher replacement content. The significant decrease in concrete self-desiccation was due to the pore structure of the 20 μm-RHA, especially the volume of mesopores.